The epidemiological situation of coronavirus infection (COVID-19) in the Republic of Dagestan and measures to reduce it - L. U. Ulukhanova; N. S. Karnaeva; M. E. Dzhabrailova; S. G. Agaeva; A. G. Gadzhimirzaeva (LLC "Diagnostics and Vaccines", 2022)
The article shows the epidemiological situation of the coronavirus infection COVID-19 (SARS-CoV2) in the Republic of Dagestan for the period 2020-2022, according to the «Republican Center for Infectious Diseases and AIDS» of Makhachkala, Dagestan. Results. The epidemiological situation of the new coronavirus infection in the Republic of Dagestan (RD) remains unfavorable. In 2020, since the beginning of the pandemic, the «Wuhan» strain has been circulating, and since September 2020, the active circulation of the British «alpha» strain has begun. A new wave in 2021 with the highest incidence was recorded from June to September - associated with the inclusion of the Indian «delta» strain SARS-CoV-2 in the epidemic process. Strains of «omicron» that exist today are BA.1 and BA.2 may lead to hospitalization. They are still dangerous for residential people and patients with risk factors. Conclusion. Among the adult population, the largest number of cases of the disease was registered 90.7%. Three main age risk groups have been identified: the adult population from 50 to 64 years; from 65 years and older and from 40 to 49 years. The analysis of mortality by age groups also revealed the main risk groups: persons aged 50-59 years (15.12%); 60-64 years (23%) and over 65 years (55.6%). On 04.07.2022 1,557,661 people were vaccinated with the Gum-COVID-Vac, EpiVacCorona, KoviVak and Sputnik Light vaccine, including 1,377,645 people who completed vaccination.